Antiproliferative Activity of Polygonaceae Species from the Carpathian Basin against Human Cancer Cell Lines. (4th April 2012) - Lajter, Ildikó; Zupkó, István; Molnár, Judit; Jakab, Gusztáv; Balogh, Lajos; Vasas, Andrea; Hohmann, Judit
<x xml:space="preserve">Abstract</x> Aqueous and organic extracts of 27 selected species from five genera (Fallopia, Oxyria, Persicaria, Polygonum and Rumex) of the family Polygonaceae occurring in the Carpathian Basin were screened in vitro for antiproliferative activity against HeLa (cervix epithelial adenocarcinoma), A431 (skin epidermoid carcinoma) and MCF7 (breast epithelial adenocarcinoma) cells, using the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay. A total of 196 n‐hexane, chloroform, 50% methanol or water extracts of different plant parts were investigated. It was found that extracts of Polygonum hydropiper, Rumex acetosa, Rumex alpinus, Rumex aquaticus, Rumex scutatus and Rumex thyrsiflorus at 10 or 30 µg/mL demonstrated substantial cell growth inhibitory activity (at least 50% inhibition of cell proliferation) against one or more cell lines. R. acetosa and R. thyrsiflorus proved to be the most active and are considered worthy of activity‐guided phytochemical investigations. Copyright © 2012 John Wiley & Sons, Ltd.